Resilience in Times Of Pandemic: Is the Public Procurement Legal Framework Fit for Purpose? - Laura Alexandra Farca; Dacian Dragos (Transylvanian Review of Administrative Sciences, 2020)
This article aims to analyze whether the legislation enacted in the field of public procurement in Romania, based on the 2014 EU Directives, is effective in fostering resilience of the public institutions and indirectly of communities, and to provide a fit-for-purpose mechanism for dealing with the pandemic generated by the new type of coronavirus, Sars-CoV-2. The article discusses the necessity of new rules meant to promote swiftly purchases during the state of emergency. Undoubtedly, the pandemic generated crisis has raised some serious challenges to which public procurement regulations is in principle properly equipped to deal with: urgent need for supplies, works and services, but also unemployment or protection of other disadvantaged categories of people. We argue that resorting to specific tools (negotiated procedures, framework-agreements, centralized procurement, sustainable and social procurement, reserved contracts) when carrying out swift interventions generated by the pandemic would have been more suitable during this health crisis or even for preventing the effects of this pandemic. Instead, the attention of the legislator has been concentrated only on (unnecessarily) exempting the swift purchases of medical equipment from the rule of law.